Perspectives of Indian medical students on e-learning as a tool for medical education in the country: a quantitative study - Lawande, Neel N.; Kenkre, Trusha D.; Mendes, Nuala A.; Dias, Lydia M.; Dias, Amit S. (International Journal Of Community Medicine And Public Health, 2020)
Background: In view of the COVID-19 pandemic, medical colleges resorted to e-learning to continue teaching; giving us a unique opportunity to explore the potential of this tool, understand the student perspective, help improve its structure and assess its scope for future use. Methods: A quantitative cross-sectional study was conducted across Indian medical colleges using Google forms. The questionnaire consisted of sections on e-learning experience, technological readiness, effects of COVID-19 on education and attitude towards e-learning. Results: From 32 medical colleges in India, 556 undergraduate medical students participated in the study. The results showed that 93.3% students were exposed to e-learning, from which 99% were introduced to it following the COVID-19 pandemic-imposed lockdown. The study reported the pros and cons of e-learning for medical education. E-learning methods were deemed fit for theory lectures, but wasn’t preferred for clinics and demonstrations. Students believed that e-learning- preferably short live online classes, together with efficient portals, provision of offline videos and discussion of clinical cases- had great scope to support the traditional methods of teaching. Conclusions: According to the students, e-learning has immense potential and is an irreplaceable ally to the traditional method of medical education, even beyond the COVID-19 pandemic.